2016
DOI: 10.3389/fpls.2016.01317
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Identifies Putative Genes Involved in the Biosynthesis of Xanthanolides in Xanthium strumarium L.

Abstract: Xanthium strumarium L. is a traditional Chinese herb belonging to the Asteraceae family. The major bioactive components of this plant are sesquiterpene lactones (STLs), which include the xanthanolides. To date, the biogenesis of xanthanolides, especially their downstream pathway, remains largely unknown. In X. strumarium, xanthanolides primarily accumulate in its glandular trichomes. To identify putative gene candidates involved in the biosynthesis of xanthanolides, three X. strumarium transcriptomes, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Last year, 70 highly expressed CYP450s in the Xanthium strumarium trichomes were studied using an extensive analysis of transcriptomes. Among them, four CYP71 members (CYP71AV14, CYP71BL7, CYP71DD1, and CYP71AX30) were found to be the candidates involved in sesquiterpene lactone biosynthesis (Li et al, 2016 ). Transcriptome identification of genes for Taxol biosynthesis has been studied, however, no study has demonstrated interest in the CYP450 genes of Taxus (Wu et al, 2011 ; Sun et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Last year, 70 highly expressed CYP450s in the Xanthium strumarium trichomes were studied using an extensive analysis of transcriptomes. Among them, four CYP71 members (CYP71AV14, CYP71BL7, CYP71DD1, and CYP71AX30) were found to be the candidates involved in sesquiterpene lactone biosynthesis (Li et al, 2016 ). Transcriptome identification of genes for Taxol biosynthesis has been studied, however, no study has demonstrated interest in the CYP450 genes of Taxus (Wu et al, 2011 ; Sun et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…5a, Supplemental Data 2). One of the closest homologs to CYP71AX36 is CYP71AX30 from Xanthium strumarium , which was recently considered as a candidate for the involvement in STL metabolism based on gene expression studies 13 . A search for sub-genomic localization revealed that all enzymes thus far characterized in the STL metabolism of Helianthus annuus , are scattered across the genome 3 (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has shown inhibitory activities against several tumor cells, including breast cancer [6], colorectal cancer [7], and glioma cells [8]. In spite of many studies concerning the medical activities of xanthatin, the genes and enzymes involved in its biosynthesis are largely unknown [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nothing is known about the later stages of xanthatin biosynthesis after the formation of germacrene A. However, judging from the structure of xanthatin, the steps from germacrene A to xanthatin presumably include multiple oxidations, and enzymes of cytochrome P450s and alcohol and aldehyde dehydrogenases may be involved in these oxidation steps [9]. The specific accumulation of xanthatin in X. strumarium trichomes indicates that the trichome may be site for transcribing the xanthatin biosynthetic genes [15].…”
Section: Introductionmentioning
confidence: 99%